Femoral pseudoaneurysm as a complication of slipped capital femoral epiphysis treatment - Carlos Roberto Schwartsmann; João Pedro Farina Brunelli; Gabriel Severo da Silva; Silvio Coelho (Revista Brasileira de Ortopedia)
ABSTRACT Slipped capital femoral epiphysis is a very frequently seen condition in orthopedics centers worldwide. Even in successfully treated cases, complications related either with the pathology per se or with the chosen synthesis method are not rare. This report presents a case of bilateral slipped capital femoral epiphysis treated with pinning, in which one of the limbs developed a very rare condition: the formation of a femoral pseudoaneurysm that ruptured.